Tracing the earliest recorded concepts of international law : the ancient Near East (2500-330 BCE) - Altman, Amnon, 1935-2016 (Legal history library. Studies in the history of international law, 2012)
This book offers a unique survey of legal practices and ideas relating to international relations in the Ancient Near East between 2500 and 330 BC.